Improving Students’ Writing Skill through Project-Based Learning, Process Writing, and Instagram - Khulel, Buyun (Universitas Muhammadiyah Mataram, 2022)
The goal of this joint classroom action research was to help students enhance their capacity to write hortatory exposition texts. It involved 33 high school students as research participants. The data collection device in this study was a writing test. According to the findings of the study, combining project-based learning with process writing and Instagram could help students improve their writing skills. Students can improve their average writing score if it is higher than the passing grade. All of the students were able to improve their writing score by at least ten points over their previous score on the first test. Furthermore, 81,8% of the students were able to get the minimum passing mark.